Mentoring Bilingual Teachers in Content and Language-Integrated Learning Programs Through the SIOP - Bárcena-Toyos, Patricia (IGI Global, 2024)
The chapter examines the perceptions of novice bilingual teachers about the potential use of the SIOP as a mentoring tool that can assist them in the attention to language and the integration of academic language in their lessons. The participants (n=32) were in-service teachers enrolled in a master's program on bilingual education in an online university in Spain, with little to no experience teaching in bilingual programs. Answers to a Likert-scale questionnaire showed that participants' perceptions on mentoring programs for novice teachers in bilingual settings were overall positive. Comparisons between groups did not show any differences, which led to the conclusion that despite their previous teaching experience and their training on the CLIL approach, novice teachers still feel the need of guidance in their first encounters with teaching content and language integrated, and that the SIOP can act as an effective mentoring tool where mentoring programs are not in place.
Es un capítulo del libro: Miller, J. & Otcu-Grillman, B. (Eds.). (2023). Mentoring and Reflective Teachers in ESOL and Bilingual Education. IGI Global.
Keywords: bilingual education; SIOP Model; mentoring programs; Scopus